Morphology and population of binary asteroid impact craters - Miljkovic, Katarina; Collins, G; Mannick, Sahil; Bland, Philip (Elsevier Science BV, 2013)
Observational data show that in the Near Earth Asteroid (NEA) region 15% of asteroids are binary. However, the observed number of plausible doublet craters is 2–4% on Earth and 2–3% on Mars. This discrepancy between the percentage of binary asteroids and doublets on Earth and Mars may imply that not all binary systems form a clearly distinguishable doublet crater owing to insufficient separation between the binary components at the point of impact. We simulate the crater morphology formed in close binary asteroid impacts in a planetary environment and the range of possible crater morphologies includes: single (circular or elliptical) craters, overlapping (tear-drop or peanut shaped) craters, as well as clearly distinct, doublet craters. While the majority of binary asteroids impacting Earth or Mars should form a single, circular crater, about one in four are expected to form elongated or overlapping impact craters and one in six are expected to be doublets. This implies that doublets are formed in approximately 2% of all asteroid impacts on Earth and that elongated or overlapping binary impact craters are under-represented in the terrestrial crater record. The classification of a complete range of binary asteroid impact crater structures provides a template for binary asteroid impact crater morphologies, which can help in identifying planetary surface features observed by remote sensing.